2015
DOI: 10.1103/physrevd.92.094007
|View full text |Cite
|
Sign up to set email alerts
|

Transverse momentum resummation for dijet correlation in hadronic collisions

Abstract: We study the transverse momentum resummation for the azimuthal angular correlation in dijet production in hadron collisions based on the Collins-Soper-Sterman formalism. The complete oneloop calculations are carried out in the collinear framework for the differential cross sections at low imbalance transverse momentum between the two jets. Important cross checks are performed to demonstrate that the soft divergences are cancelled out between different diagrams, and in particular, for those associated with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 42 publications
4
84
1
Order By: Relevance
“…We believe this results can help to quantitatively study the BFKL dynamics through Mueller-Navelet jets production at the LHC. Last but not least, we would like to comment on the recent studies of the transverse momentum resummation for generic dijet production in hardon-hadron collisions [32][33][34]. It has been shown that the Sudakov resummation is playing an important role in describing JHEP03(2016)096 the dijet correlation data at both the Tevatron and the LHC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We believe this results can help to quantitatively study the BFKL dynamics through Mueller-Navelet jets production at the LHC. Last but not least, we would like to comment on the recent studies of the transverse momentum resummation for generic dijet production in hardon-hadron collisions [32][33][34]. It has been shown that the Sudakov resummation is playing an important role in describing JHEP03(2016)096 the dijet correlation data at both the Tevatron and the LHC.…”
Section: Discussionmentioning
confidence: 99%
“…In the dijet production process, final state radiation will also contribute to the single logarithms which will depend on the jet cone size. In general kinematics of dijet production, the TMD resummation is much more complicated than the above equation, where a matrix form has to be included to take into account final state radiation contributions [32][33][34]. However, in the current case, because of the two jets are produced with large rapidity separation, the resummation formula will be much simplified.…”
Section: Jhep03(2016)096mentioning
confidence: 99%
See 3 more Smart Citations